2012
DOI: 10.1175/jpo-d-11-0137.1
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Stability in a Large-Scale Internal Wave Shear

Abstract: The effect of a large-scale internal wave on a multipolar compound vortex was simulated numerically using a 3D Boussinesq pseudospectral model. A suite of simulations tested the effect of a background internal wave of various strengths, including a simulation with only a vortex. Without the background wave, the vortex remained apparently stable for many hundreds of inertial periods but then split into two dipoles. With increasing background wave amplitude, and hence shear, dipole splitting occurred earlier and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
(99 reference statements)
1
12
0
Order By: Relevance
“…Several other studies (Smyth & McWilliams 1998;Brunner-Suzuki et al 2012;Dritschel & Mckiver 2015;Tsang & Dritschel 2015) have shown numerically that the stability properties and some aspects of the dynamics of vortices in rotating, stratified flows are not very sensitive to the specific value of f /N as long as this value is small. Here, we show numerically that the eigenvectors and eigenvalues of Gaussian vortices (with N 2 c > 0), when properly scaled, are nearly independent of f /N for small f /N .…”
Section: Effect Of F /N On Linear Stabilitymentioning
confidence: 97%
See 2 more Smart Citations
“…Several other studies (Smyth & McWilliams 1998;Brunner-Suzuki et al 2012;Dritschel & Mckiver 2015;Tsang & Dritschel 2015) have shown numerically that the stability properties and some aspects of the dynamics of vortices in rotating, stratified flows are not very sensitive to the specific value of f /N as long as this value is small. Here, we show numerically that the eigenvectors and eigenvalues of Gaussian vortices (with N 2 c > 0), when properly scaled, are nearly independent of f /N for small f /N .…”
Section: Effect Of F /N On Linear Stabilitymentioning
confidence: 97%
“…Like many other studies, for most cases we have used f /N = 0.1, rather than f /N = 0.01 (which is a better representative of the mid-latitude oceans, see Chelton et al (1998); ), because small values of f /N are computationally expensive to tackle (see, e.g., Brunner-Suzuki et al 2012;Tsang & Dritschel 2015). However in this paper, we use the semi-analytic method of Barranco & Marcus (2006), which allows us to compute flows efficiently for a wide range of f /N , including the more physically relevant value of 0.01.…”
Section: Parameter Map Of Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Additional structural details of mixed patches can be inferred from our figures (see section 3), but these are not our main focus. The interested reader is referred to Lelong and Sundermeyer (2005) and Brunner-Suzuki et al (2012). In our primary simulations (Table 2, runs A-E), mixed patches are assumed fully mixed at their centers (i.e., DN /N 2 5 1), yielding a time-and volume-averaged energy dissipation rate of approximately 8 3 10 28 W kg 21 .…”
Section: B Initial Conditions and Forcingmentioning
confidence: 99%
“…An S vortex is unstable by itself, owing to vertical variations of its meridional PV (Flierl 1988;Morel and McWilliams 1997) as well as its horizontal PV (Kloosterziel and Carnevale 1999;Beckers et al 2003). Furthermore, when perturbed by a large-scale internal wave, an S vortex will break into dipoles, with time to breakup decreasing with increasing internal wave strength (Brunner-Suzuki et al 2012). Resulting dipoles have smaller horizontal diameter than the original S vortex, indicating a downscale energy transfer, counter to the canonical vortexinduced upscale transfer.…”
Section: Introductionmentioning
confidence: 99%